Unity 5 for beginners - Thorn, Alan; Safari eBooks ([Place of publication not identified] : Packt Publishing, 2016)
"Unity Fundamentals is an easy-to-follow exploration of the Unity foundations. It covers the core features every developer needs to know to work effectively. Using practical and hands-on examples, Alan Thorn explores how Unity can be applied creatively to build exciting games that sell."--Resource description page.
Title from title screen (viewed September 16, 2016).
Presenter, Alan Thorn.
Keywords: Unity (Electronic resource); Video games -- Design; Electronic books